Automatic tuning of Q-enhanced integrated differential bandpass filters in a silicon-on-sapphire process - Strouts, Renee (Kansas State University, 2009)
In microchip circuitry, the tiny size of inductors creates low Q values, limiting a bandpass filter’s ability to have narrow bandwidths at RF frequencies. To counter this problem and also compensate for losses, Q-enhancement can be implemented to facilitate narrower bandwidths and boost gain. With Q-enhancement, temperature sensitivity of the circuitry causes the filter parameters to drift over time, making it necessary to adjust the filter periodically in order to keep the filter centered at the desired frequency. With the proper additional on-chip circuits used with a microprocessor, a tuning algorithm makes it possible to automatically tune the filter in-situ. The algorithm is based on increasing Q-enhancement until the filter begins to oscillate, reading the frequency of oscillation, adjusting to the desired frequency, and then decreasing Q-enhancement until the filter no longer oscillates. A 500MHz single-pole differential filter was designed with an on-chip amplitude detector and frequency prescaler to facilitate tuning. The filter was made adjustable across frequency with banks of binary weighted switchable capacitors. Q-enhancement adjustment was achieved via banks of cross-coupled FETs, also binary weighted. The circuit was fabricated in 0.5μm silicon-on-sapphire technology. The finished filter chip was controlled with a PIC microprocessor which had been programmed in C with the tuning algorithm. With the tuning algorithm in place, the filter was successfully able to align itself to within ±1MHz of the desired 500MHz center frequency. Q-enhancement levels were also able to self-adjust to maintain a desired bandwidth. An improved design based around an off-chip coupled-resonator two-pole filter has also been designed. This filter includes adjustable coupling capacitance between the two poles, which also must be tuned. A new method of tuning is proposed for such applications. The properties of a two-pole filter cause it to oscillate at two frequencies with Q-enhancement. A modified amplitude detector is capable of reading the beat frequency which results from the two oscillations, a value which relates directly to and allows tuning of the bandwidth of the filter.
Keywords: Automatic tuning; Q-enhanced; Filter; Engineering, Electronics and Electrical (0544)